The factors influence customer’s intention to use green product - Ahmad Azri Hassan; Aiza Izyani Zulkuple; Asmieyda Azman; Catherine Chong Siaw Ying (2016)
Green brand is a process of creating environment friendly product that safe from different hazards. Nowadays, climate change has become a global concern prior to the irresponsible human activities. Community knows how to use the product on the physical look rather than thinking about the side-effect that they will get when they used the product. As the environment continues to worsen, it has become a persistent public concern in the awaken developing countries to the green movement. This study aimed to analysis the relationship between brand awareness, brand trust, brand image, perceived value, brand satisfaction and customer’s intention to use green products. Which of the factors give the most impact to customer’s intention to use green product. Questionnaires were distributed to collect the responses from 346 sample of respondents in Pengkalan Chepa, Kelantan by regard that respondents that respondents are aware with environment-related activities. Data was analysed according on descriptive analysis, reliability test, correlation analysis and simple regression analysis. For regression analysis, we involved all that data into SPSS and do analysis also. This study found that brand awareness and brand trust among community were low due to of their lifestyle. It can be more tends to ones to one product if there are trusting it. The conclusion that was drawn is that, there are positive relationship between brand awareness, brand trust, band image, perceived value, brand satisfaction and customer’s intention to use green products. These factors influence customer’s intention to use green product. it will crucial for government and marketers to work closely not just to create better awareness on the green eco-labelling and certification among Malaysians as well as to transform consumer knowledge on environment issues as a strong platform to practice an ethical uses.